Penyelesaian Sengketa atas Video dan Foto Resepsi Pernikahan Hilang Perspektif Kompilasi Hukum Ekonomi Syariah - Aricanes, Erisando; Zahara, Fatimah (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2024)
Settlement of disputes in al-ijarah contract transactions between service providers (mu'jir) and service recipients (musta'jir) in Medan City, is sometimes carried out not in accordance with the instructions contained in Supreme Court Regulation Number 02 of 2008 concerning the Compilation of Sharia Economic Law (KHES). This can be seen, when a musta'jir in the city of Medan demands compensation from the mu'jir with an amount that is very burdensome for the mu'jir, even though the actual condition of the mu'jir is not breaking a promise, but because of a compelling or emergency condition caused by losing your laptop, burning your hard disk, or video and photo files being infected by a virus so that the data is lost and it is difficult to restore the data to how it was originally. Mu'jir has broken his promise if seen at a glance as stated in Article 36 starting from letter "a" to letter "d", but does not necessarily have to bear all the risks from the loss of videos and photos of the wedding reception. There are conditions that are not fulfilled in accordance with those contained in Article 39 of Supreme Court Regulation Number 02 of 2008 concerning the Compilation of Sharia Economic Law (KHES) in declaring a mu'jir breaking his promise, the first condition is that the mu'jir never makes the same mistake twice, and secondly mu'jir in conditions of necessity or emergency that cannot be avoided.